A IMPORTÂNCIA DO PROCESSO COMUNICACIONAL NA GESTÃO DA MODALIDADE EAD ESTUDO DE CASO UNIVERSIDADE METODISTA DE SÃO PAULO - Somensari, Patricia (2012)
The higher education institutions focused on distance learning mode have in its management structure some communication and language mechanisms. The online communication form in distance learning mode must prioritize the quality of message reception and identification to obtain success in learning process and a better interpretation of stakeholder s cultural aspects, among professors and students. Based on that, the objective of this research is to find mechanisms for better communication and upgrading for language in the virtual learning environment. In order to recognize possible trends in management and before the changes of modern society, education institutions embraced distance learning mode and also, with globalization, this mode of education was inserted in daily life of individuals. The Methodist University of São Paulo following examples of foreign universities also adopted distance learning and its procedures. It presents many differences in their management of teaching and learning form compared to a classroom course. The study is a qualitative research methodology, accomplished through a case study. Data analysis was developed through structured interviews. The questions are extremely clear and discusses the daily routine of individuals involved regarding involvement with the theme The selection of the sample is comprising for thematic teachers, employees and students belonging to the institution, whom are inserted in distance learning mode. The coupling of the study of culture ally with forms of communication and language, using criteria for management, demands a research with items related to education and means of learning. The research involves many important studies relating to the either management education, as to the language and individual communication. Finishing the dissertation, subject to the communication may be compromised if the dialogue does not exist with frequency and so undertakes the communication process.(AU)